The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/nar/gki164
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 gene expression by retroviral vector-mediated small-guide RNAs that direct specific RNA cleavage by tRNase ZL

Abstract: The tRNA 3′-processing endoribonuclease (tRNase Z or 3′ tRNase; EC 3.1.26.11) is an essential enzyme that removes the 3′ trailer from pre-tRNA. The long form (tRNase ZL) can cleave a target RNA in vitro at the site directed by an appropriate small-guide RNA (sgRNA). Here, we investigated whether this sgRNA/tRNase ZL strategy could be applied to gene therapy for AIDS. We tested the ability of four sgRNA-expression plasmids to inhibit HIV-1 gene expression in COS cells, using a transient-expression assay. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Taken together, these results suggest that gene-silencing efficiency of sgRNA would generally Gene silencing by tRNase Z L and sgRNA A Nakashima et al become comparable to that of siRNA as an sgRNA amount is increased. tRNase Z L is responsible for the gene silencing by sgRNA Although these and previous results 15,16 indicated that appropriate sgRNAs can downregulate targeted gene expressions in the cells, no direct evidence existed demonstrating that the downregulation is owing to specific mRNA cleavage by endogenous tRNase Z L not owing to a simple antisense effect or other different mechanisms. To clarify this issue, we generated two types of stable 293 cell line, which produce more tRNase Z L or less tRNase Z L and examined silencing levels for the luciferase gene in these transfectants.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Taken together, these results suggest that gene-silencing efficiency of sgRNA would generally Gene silencing by tRNase Z L and sgRNA A Nakashima et al become comparable to that of siRNA as an sgRNA amount is increased. tRNase Z L is responsible for the gene silencing by sgRNA Although these and previous results 15,16 indicated that appropriate sgRNAs can downregulate targeted gene expressions in the cells, no direct evidence existed demonstrating that the downregulation is owing to specific mRNA cleavage by endogenous tRNase Z L not owing to a simple antisense effect or other different mechanisms. To clarify this issue, we generated two types of stable 293 cell line, which produce more tRNase Z L or less tRNase Z L and examined silencing levels for the luciferase gene in these transfectants.…”
Section: Resultsmentioning
confidence: 64%
“…4,6 We have shown the efficacy of this RNA-targeting method in the living cells to some degree by introducing sgRNAs either as their expression plasmids or as 2 0 -Omethyl RNAs. 15,16 The expression of exogenous reporter genes for Escherichia coli chloramphenicol acetyltransferase (CAT) and firefly luciferase were downregulated by appropriately designed sgRNAs in mammalian culture cells, 15 and the HIV-1 expression in Jurkat cells was almost completely suppressed by a 5 0 -half-tRNA-type sgRNA up to 18 days. 16 However, the involvement of tRNase Z L in this gene silencing remained unproven.…”
Section: Introductionmentioning
confidence: 99%
“…Mo-MLV-based sgRNA-SL4 targeting the HIV-1 gag gene could suppress sgRNA-dependent HIV-1 expression in human T cells. [23] In this article, we demonstrate the combinatorial action of RNase P and tRNase ZL-mediated specific inhibition of HIV-1 in cultured cells. We designed two truncated short extra guide sequences (sEGS) specifically recognize the tat and vif regions of HIV-1 mRNA and mediate subsequent cleavage of hybridized mRNA by the RNase P and tRNase ZL components.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, we demonstrated the inhibition of HIV-1 gene products in cultured cells by inducing HIV-1 mRNA cleavage using a modified 5 -half-tRNA Arg (sgRNA) and mammalian tRNase ZL. [23] The greatest inhibitory effect on HIV-1 expression was achieved using sgRNA targeting the HIV-1 gag gene.…”
Section: Design and Construction Of The U6-egs Driven Expression Systemmentioning
confidence: 99%
“…The present results together with this observation imply that other types of small cellular ncRNA would also mediate regulation of gene expression by tRNase Z L . It is now clear that the reason why the TRUE gene silencing method works well in the cells [14][15][16][17] is because it utilizes artificial sgRNAs like naturally occurring ncRNAs and mimics the intrinsic cellular gene regulatory system. …”
Section: A New Mechanism For Mirna-mediated Silencingmentioning
confidence: 99%